SASTRA CETAK AWAL HINDIA BELANDA DI SEMARANG - Handayani, Pipit Mugi; Arifin, Zainal (HISKI, 2023)
This research was conducted to trace the development of printed literature at the beginning of the Dutch East Indies Government. This study aimed to identify printed Malay language documents found in libraries throughout Central Java,especially in Semarang, which was printed before World War II, focusing on the period 1820-1940 (the colonial era and the growth of print literacy in Malays). The categorization of literary publishers was attempted to characterize the development of printed literature in the Dutch East Indies. Qualitative research methods with descriptive qualitative analysis techniques were used to convey accurate data obtained from library studies and field data in the form of printing and publishing data in the form of lists of newspapers printed during the Early Dutch East Indies around 1880-1945.qualitative research methods with descriptive qualitative analysis techniques by conveying accurate data obtained from library studies and field data in the form of printing and publishing data in the form of lists of newspapers printed during the Early Dutch East Indies around 1880-1945. To trace the development of early printed literature in the Dutch East Indies, data were obtained from several publications and printers that printed newspapers, brochures, and books on politics, health, and literature. Several sources obtained results related to data on the number of publications or printing presses in Semarang as well as the newspapers printed by these printing presses. The conclusion of this research is that the initial development of printed literature began with the presence of various printing and publishing houses. It was recorded that there were 16 publishing and printing companies operating over a period of 100 years from 1845-1945 to. Early printed literature in the Dutch East Indies usually took the form of newspapers or books. There are approximately 19 newspapers which are daily or weekly which are published and used very well by the Dutch government as promotional, educational and even propaganda media. Of the many publications and printers that exist and thrive in Semarang, only a few print literary works in the form of books and newspapers. It is known that there are only three printers or publishers that print literary books: G.C.T. van Dorp Co., Semarang Drukkerij en Boekhandel H. A. Benjamins and NV Boekahandelen, Drukkerij Masman and Stroink.AbstrakPenelitian ini dilakukan dalam upaya penelusuran perkembangan sastra cetak di awal Pemerintahan Hindia Belanda. Penelitian ini bertujuan mengetahui bagaimana dokumen cetakan berbahasa Melayu yang terdapat di perpustakaan di seluruh di Jawa Tengah, Terkhusus di Semarang. yang dicetak pada masa sebelum Perang Dunia II. dalam kurun waktu 1820-1940 (zaman kolonial dan pertumbuhan keberaksaraan cetak di Melayu), dan bagaimanapengategorisasian penerbit-penerbit sastra diupayakan sebagai sumber pembabakan perkembangan sastra cetak masa Hindia Belanda. Penelitian ini menggunakan metode penelitian kualitatif dengan teknis analisis deskriptif kualitatif dengan menyampaikan data-data akurat yang didapatkan dari studi pustaka dan data lapangan berupa data percetakan dan penerbitan berupa daftar surat kabar yang dicetak pada masa Hindia Belanda awal sekitar tahun 1880-1945-an. Pada penelusuran perkembangan sastra cetak awal Hindia Belanda, didapatkan data beberapa penerbitan dan percetakan yang mencetak surat kabar, brosur dan buku baik politik, kesehatan, maupun sastra. Beberapa sumber diperoleh hasil terkait data jumlah penerbitan atau percetakan yang berada di Semarang serta surat kabar yang dicetak oleh percetakan-percetakan tersebut. Temuan penelitian ini adalah perkembangan awal sastra cetak dimulai dengan hadirnya berbagai percetakan dan penerbitan. Tercatat ada 16 perusahaan penerbitan dan percetakan yang beroperasi pada kisaran waktu 100 tahun dari 1845-1945. Sastra cetak awal Hindia Belanda biasanya berbentuk surat kabar atau buku sastra. Terdapat lebih kurang 19 surat kabar yang merupakan harian atau mingguan yang terbit dan dimanfaatkan dengan sangat baik oleh pemerinah Belanda sebagai media promosi, edukasi bahkan propaganda. Dari sekian banyak penerbitan dan percetakan yang ada dan tumbuh berkembang di Semarang tersebut, hanya sedikit yang mencetak karya sastra dalam bentuk buku atau surat kabar. Diketahui hanya ada tiga percetakan atau penerbit yang mencetak buku literatur di antaranya G.C.T. van Dorp Co., Semarang Drukkerij en Boekhandel H. A. Benjamins dan NV Boekahandelen Drukkerij Masman dan Stroink.